Flash mob tools in science communication - How can we reach the young generation? - Kuráth, Gabriella; Kosaras, Attila; Szuhán-Glass, Beáta; Bánkyné Perjés, Beatrix (The Hungarian Journal of Marketing and Management, 2019)
The generations are changing, the differences are significant, the presentation of scientific life and making it tangible is increasingly difficult using the traditional marketing and communication methods. Therefore, the organizations dealing with science communication, including higher educational institutions, should reflect the ideas evolved about the target groups and their availability since the methods and tools of science communication need to follow the changes. The main aim of our project was to present the scientific achievements of the University of Pécs and the values of the work carried out here to the young generation found in the institution’s catchment area. Therefore our study includes the possibilities of communication with young generation, the main features of the tools used by us, summarizing the main results and recommendations.